Perceived Changes in Environmental Degradation and Loss of Ecosystem Services, and Their Implications in Human Well-Being - Zorondo-Rodriguez, F (Taylor and Francis Ltd., 2017)
Rural communities worldwide face a decrease of critical ecosystem services caused by replacement of native forests by commercial plantations. Replacement of native forest by commercial plantations decreases water provisioning, with possible negative impacts over well-being. We tested this hypothesis in Central Chile. We assessed subjective well-being (SWB) and local perceptions of changes in forest cover and water provision among 78 rural families. We also assessed if the Shifting Baseline Syndrome (SBS) affects the perceptions of environmental changes and their implications in SWB. Individuals perceived less forest cover than 20 years ago, and this is seen as a factor of decreased livelihood, availability of forest products, and water provisioning for households. People also reported less water available than 20 years ago. The main drivers associated with decreased water provision were the establishment of pine plantations (44% of individuals) and drought (44%). A better-off SWB was associated with perception of lower rate of deforestation. The perceptions of forest degradation and its association to SWB are affected by SBS. Paradoxically, a better-off SWB was also associated with an improvement of water quality, although the quantity and quality of water have decreased according to biophysical data, which ought to decrease the SWB. Impacts of environmental degradation in SWB are masked by factors such as more infrastructure for drinking water, assisted by governments. This masking of environmental degradation reduces the opportunity to avoid negative impacts over well-being among rural communities that are dependent on assistance around the world. © 2016 Informa UK Limited, trading as Taylor & Francis Group.